PEMANFAATAN BIOCHAR SEKAM DAN KOMPOS JERAMI PADI TERHADAP PERKECAMBAHAN BENIH CENDANA (Santalum album Linn.) - Firdaustian Aka Heku; Wilhelmina Seran; Norman P. L. B. Riwu Kaho (Jurnal Celebica : Jurnal Kehutanan Indonesia, 2024)
Sandalwood (Santalum album Linn.) is a forest wood-producing plant in East Nusa Tenggara (ENT) province that has high economic value and is an endemic species. Efforts to restored sandalwood plants in ENT have been carried out, such as development efforts by planting sandalwood from nurseries, as well as maintaining saplings that comes from natural spreading, but these efforts has not been successful enough. Giving rice husk biochar and rice straw compost in planting media can increased the availability of phosphorus (P), nitrogen (N), potassium (K), sulfur (S), calcium (Ca) and magnesium (Mg).The method used in this study is Complete Randomized Design (RAL) with a comparison of the composition of the planting media used (M0) Soil 100% Control 10 Kg, (M1) Soil 50% + 50% Biochar Rice Husk, (M2) Soil 50% + 50% Rice Straw Compost, (M3) Soil 25% + 50% Rice Husk Biochar + 25% Rice Straw Compost, (M4) Soil 25% + 25% Rice Husk Biochar + 50% Rice Straw Compost, (M5) Soil 50% + 25% Rice Husk Biochar + 25% Rice Straw Compost.The results of this study showed that the germination percentage value was 38.67% in M4 treatment. M4 treatment with a ratio of soil planting media 25% + 25% Rice Husk Biochar + 50% Rice Straw Compost, provides the highest average increase and has a very significant effects on germination, germination rate index, and germination value.